2012
DOI: 10.1177/0192623311436175
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Passages of Göttingen Minipigs from the Neonatal Period to Young Adult

Abstract: Histopathological examination of the nasal passages requires a standardized approach for recording lesion distribution patterns. Nasal diagrams provide guidance to map the lesions. Information on lesions exists for rodents, dogs, and monkeys, which all have been used in inhalation studies. Recently, minipigs have garnered interest as an inhalation model because minipigs resemble humans in many features of anatomy, physiology, and biochemistry and may be a good alternative to monkeys and dogs. The present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In this study, we examined five cross sections of the nasal cavities of Bama minipigs; section selection was based on the presence of the main nasal structures and of distinct representative epithelial areas, although the landmarks used differed from those reported for Göttingen minipigs [22]. Our approach was geared toward observation of the general histological and anatomical structures of the nasal cavity of Bama minipigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined five cross sections of the nasal cavities of Bama minipigs; section selection was based on the presence of the main nasal structures and of distinct representative epithelial areas, although the landmarks used differed from those reported for Göttingen minipigs [22]. Our approach was geared toward observation of the general histological and anatomical structures of the nasal cavity of Bama minipigs.…”
Section: Discussionmentioning
confidence: 99%
“…The NALT in rodents consists of pairs of lymphoid tissues located in the floor of the nasal cavity [26]. We observed that, in the noses of Bama minipigs, the NALT is located adjacent to the nasopharyngeal meatus roof, and is continuous with pharynx lymphoid tissue, similar to the nasopharyngeal tonsils of Göttingen minipigs and humans [22]. Lymphoid follicles, as part of the NALT, were accumulated in random areas within the nasal mucosa of the Bama minipigs tested.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate, we tried to develop an accurate method of objectively quantifying the images. The other limitation was that the anteriorly located solution could not be affected by mucociliary movement as the histologic characteristics of the nasal passages of young pig showed a transitional epithelium, except for the squamous epithelium at the tip of the turbinate and the respiratory epithelium at the dorsal base of the turbinate . Even when we administrated the solution targeting the dorsal portion of the turbinate, some solution could still flow down and deposit on the transitional epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…167 The nasal cavity is structurally complex, reflecting the diverse physiological functions associated with this anatomical site. Kuper et al 168 provide an overview of normal nasal passages of Gottingen minipigs from the neonatal period to young adult. Several additional articles describe the anatomy and histology of porcine nasal cavity tissues.…”
Section: Nasal Cavitymentioning
confidence: 99%
“…For inhalation studies, Albl et al recommend 2 additional frontal sections of the nasal septum and turbinates (caudal to the first incisors and caudal end of turbinates) to examine squamous and transitional epithelium. Kuper et al 168 provide additional guidance for a standard method to sample the minipig nasal passages, including a section of the nasopharynx to examine NALT. The importance of consistent sampling cannot be overemphasized in evaluation of the nasal cavity since normal changes in epithelial type with location may be mistaken for xenobiotic-induced lesions.…”
Section: Nasal Cavitymentioning
confidence: 99%